Music, learning and early childhood education: a review of literature - Mangwaya, Ezron (Infinity, 2016)
Oftentimes teachers consider learning in the formal classroom as the best approach to teaching early childhood learners. Activities such as music and dance are usually regarded as opportunities for relaxation and therefore not useful as tools for effective teaching and learning. This review of literature demonstrates that singing or music as it is currently known provides invaluable avenues for concept acquisition across the early childhood school curriculum. The review thus proposes various ways which early childhood education teachers can adopt in using music as an avenue for effective teaching and learning